High cardiovascular risk of patients with type 2 diabetes is only partially attributed to angiographic burden of atherosclerosis. (September 2020) - Battermann, Simone; Milzi, Andrea; Dettori, Rosalia; Burgmaier, Kathrin; Marx, Nikolaus; Burgmaier, Mathias; Reith, Sebastian
Background: Patients with type 2 diabetes (T2DM) are at high risk for cardiovascular events and present more severe coronary artery disease (CAD). The Gensini and COURAGE scores are established angiographic instruments to assess CAD severity, which may also predict future cardiovascular risk. However, it is unclear if these scores are able to depict the increased risk of patients with T2DM and stable CAD (T2DM-SAP). Methods: We performed quantitative coronary angiography and assessed the Gensini and COURAGE scores in 124 patients with T2DM-SAP. Angiographic data were compared to patients with stable angina without T2DM (Non-DM-SAP, n = 74), and to patients with acute coronary syndrome and T2DM (T2DM-ACS, n = 53). Results: T2DM-SAP patients had similar Gensini and COURAGE-scores compared to Non-DM-SAP-patients (Gensini: 14.44 ± 27.34 vs 11.49 ± 26.99, p = 0.465; COURAGE: 3.48 ± 4.49 vs 3.60 ± 4.72, p = 0.854). In contrast, T2DM-SAP patients had significantly lower Gensini (14.44 ± 27.34 vs 30.94 ± 48.74, p = 0.003) and lower COURAGE (3.48 ± 4.49 vs 5.30 ± 4.63, p = 0.016) scores compared to T2DM-ACS-patients. Conclusion: Both the Gensini and the COURAGE score fail to predict the high cardiovascular risk of patients with T2DM-SAP. Therefore, these scores should be used with caution in the assessment of future risk of patients with T2DM. However, among T2DM-ACS patients, both scores are increased, reflecting the high cardiovascular risk in this patient population.